2021
DOI: 10.47743/jpd.2021.28.1.888
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Histoanatomical Study of Sapria Himalayana Griff. F. Albovinosa Flower Buds and Its Intersection With Its Host Plant Tetrastigma Laoticum Gagnep.

Abstract: Sapria, a holoparasitic plant of Rafflesiaceae is still understudied in term of anatomical, even more in histoanatomical study. This study aimed to perform preliminary observation on Sapria himalayana Griff. f. albovinosa morphology on its early and late stage of flower bud development inside its host, Tetrastigma laoticum Gagnep. (Vitaceae). The results show the progression from the early flower bud as it starts to grow in the host vascular cambium area towards proximal direction to reach the host xylem and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Cupule in Rafflesiaceae plants functions as a haustorium, providing nutrients and water [ 90 , 91 ]. Several histoanatomical studies described the process of teardrop-shaped protocorm penetration into the host for flowering in endophytes, and found that the haustorium of Rafflesiaceae plants starts to form in the vascular cambium of the host [ 3 , 61 , 87 , 92 ]; however, the molecular mechanism of haustorium formation is unknown. The process of haustorium formation has been well studied in Orobanchaceae, and is regulated by the LRD program genes [ 43 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cupule in Rafflesiaceae plants functions as a haustorium, providing nutrients and water [ 90 , 91 ]. Several histoanatomical studies described the process of teardrop-shaped protocorm penetration into the host for flowering in endophytes, and found that the haustorium of Rafflesiaceae plants starts to form in the vascular cambium of the host [ 3 , 61 , 87 , 92 ]; however, the molecular mechanism of haustorium formation is unknown. The process of haustorium formation has been well studied in Orobanchaceae, and is regulated by the LRD program genes [ 43 , 88 ].…”
Section: Discussionmentioning
confidence: 99%